Genesis of the national pharmaceutical legislation on the territory of modern Ukraine between IX and early XX centuries: historical and legal aspects - O. H. Aleksieiev (Aktualʹnì Pitannâ Farmacevtičnoï ì Medičnoï Nauki ta Praktiki)
The aim of the paper is to elucidate the genesis and early development of the national pharmaceutical legislation on the territory of modern Ukraine between IX and early XX centuries taking into account historical and legal aspects.